The application of double-layer remote phosphor structures in increasing WLEDs color rendering index and lumen output - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (Institute of Advanced Engineering and Science, 2020)
The remote phosphor structure often has inferior color quality but better luminous flux in than conformal or in-cup configurations. Therefore, numerous researches study remote phosphor structure for methods to enhance it chromatic quality. This study introduces the use of dual-layer remote phosphor structure in WLEDs with identical structure but at different color temperature, 6600K and 7700K, to demonstrate their effect on quality indicators. The concept is placing a green phosphor layer (Ce,Tb)MgAl11O19:Ce:Tb or a red phosphor layer MgSr3Si2O8:Eu2+,Mn2+ on the layer of yellow-emitting phosphor YAG:Ce3+ and find the suitable concentration of the additional phosphor to create the best color quality. The results showed that the increase of CRI and CQS are affected by MgSr3Si2O8:Eu2+,Mn2+, in particular, the higher the concentration of red phosphor gets the better CRI and CQS because the emitted red light in enhanced. The green phosphor layer (Ce,Tb)MgAl11O19:Ce:Tb, on the other hand, is beneficial for the luminous flux. The concentration of MgSr3Si2O8:Eu2+,Mn2+ and (Ce,Tb)MgAl11O19:Ce:Tb, however, need to be adjusted properly to avoid decreasing the luminous flux due to overgrowth. The Mie scattering theory and Beer’s law are the verification tools for these conclusions, which gives them the credibility to be applied in producing better quality WLEDs.